Profiles of early expressive vocabulary in children with typical and atypical language development - Auza-Benavides, Alejandra; Márquez-Caraveo, Maria Elena; Murata, Chiharu; Perez-Barron, Veronica (Frontiers in Communication, 2024)
The development of early childhood vocabulary is influenced by both biological and environmental factors, which shape language acquisition. This research investigates the variability in early expressive vocabulary among typically developing children (TD), Late Talkers (LTs), and those at risk for neurodevelopmental conditions like Autism Spectrum Disorder (ASD), and Developmental Language Disorder (DLD). Participants included 132 Mexican Spanish-speaking children: 37 with TD (M = 24.89, SD =4.01), 37 LTs (M = 24.78, SD 3.51), 41 at risk for ASD (M = 24.39, SD = 4.31) and 17 at risk for DLD (M = 37.71, SD = 4.50). The MacArthur-Bates Communicative Development Inventory II was utilized to assess 23 vocabulary categories, which were grouped into six broader categories (nouns, verbs, adjectives-adverbs, functional words, routines and sounds-onomatopoeias). The results indicated differences in vocabulary distribution among the groups. Although TD children generally exhibited the highest performance, there was notable variability within this group. Both LTs and children at risk for ASD showed differences compared to TD children, with LTs demonstrating the most reduced lexical usage. Children at risk for DLD and LTs displayed similar lexical profiles, characterized by reduced use of verbs and functional words. LTs and most children at risk for ASD exhibited low usage across all vocabulary categories. This analysis identified distinct vocabulary profiles among TD, LTs, ASD, and DLD groups, with variability across vocabulary categories reflecting the unique characteristics of each group. These findings enhance our understanding of the heterogeneity in early language development across clinical populations.